Characteristics, treatment, and nursing care of patients infected by Sars-CoV-2 hospitalized in intensive care units: multicenter study of colombian hospitals - Cortés, Olga L.; Vasquez, Skarlet M.; Martínez, Natalia; Esparza, Maribel; Arias, Martha; Pulido, Sandra; Rojas, Yudy A.; Mojica, Carolina; Paipa, María del Pilar; Arevalo, Indira (Investigación y Educación en Enfermería, 2023)
Objective. To describe the clinical characteristics, treatment, evolution, and nursing care of adult patients with severe acute respiratory distress syndrome who were positive for SARS-CoV-2 and hospitalized in intensive care units (ICUs) during the first peak of the pandemic in Colombia, 2020. Methods. Multicenter descriptive study of four high-complexity hospitals in Colombia, which included 473 consecutive adult patients admitted to intensive care units with a confirmed diagnosis of SARS CoV-2. Sociodemographic and clinical information - comorbidities, treatment and evolution - and nursing care provided were included. Results. Of the patients included, 43.7% died, 88.8% had pneumonia, and 60.2% developed respiratory distress syndrome. Most of those who died were men. Those who died had a median age of 68.4 years and a higher frequency of comorbidities (hypertension, cardiovascular disease, chronic obstructive pulmonary disease, and higher body mass index). They were admitted to the ICU with higher rate of dyspnea, lower oxygen saturation, and higher score of multiorgan failure. They also more often required mechanical ventilation and pronation therapy and were given more vasopressors and renal replacement therapy. Conclusion. People with severe acute respiratory distress syndrome due to COVID-19 who were hospitalized in the ICU had a high risk of death, especially older patients; males; those with cardiovascular, respiratory, and hypertension comorbidities; those who needed mechanical ventilation; and those with an elevated SOFA score. The nursing care of these critically ill patients focused on respiratory care and the prevention of associated complications.